MENINGKATKAN MINAT BACA DI KALANGAN ANAK-ANAK PANTI ASUHAN “DAARUT TAUBAH” - Ria Karina; Natalis Christian; Iskandar Itan; Erika Chen; Jacky Lim; Kian Ricardoegan; Winson Winson; Susanti Susanti; Vinco Vinco; Hartono Hartono; Willy Benyamin Ompusunggu; Erwin Erwin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Reading a book is a fun activity if someone is used to it. Instead, this activity becomes the most boring thing ever done when someone has no interest in reading books. There are two types of people when reading a book, the first is someone who likes to read books without a picture. The second type, are people who like to read books interspersed with pictures. Everyone's interest in reading a book depends on the motivation and presentation of the book itself which makes other people interested in reading. The habit of reading this book must be instilled early on. Various reading sources are widely available both in the form of books and digital content such as e-books, digital magazines, and animated videos. The role of parents and the environment is very important for the development and growth of children. Reading books has value and benefits for children in terms of children's character development. Therefore, raising awareness of the importance of reading books is important. Community service activities carried out are by donating notebooks and stationery to the people who need them and introducing them to the importance of reading culture through online educational activities.